On the possibility of a public regime in higher education: rethinking normative principles and policy frameworks - Durán Del Fierro, Francisco (Critical studies in education, 2023)
The process of reversing a neoliberal regime in highly marketised higher education systems entails the discussion of such a regime's normative principles and policy frameworks. Little has been said about what decommodification would involve or the implications of such a project for the constitution of a public regime in higher education. Two principles are discussed in this paper to delve into these concerns in detail: institutional diversity and autonomy. In addition, the role of quality policies is considered. In this respect, I critically analyse how the neoliberal regime in higher education has adopted these normative principles and policies. I claim that this regime has defined the content of the boundaries of such elements through a particular understanding of objectivity, neutrality and impartiality. Then, I discuss the plausibility of a public regime in higher education by rethinking these categories, which entails the reconsideration of the relationship between power, knowledge and subjectivity.